Perancangan Sistem Informasi Kepegawaian Berbasis Web pada PT Selaras Simpati Nusantara - Dinata, Chandra; Mardiani, Mardiani (MDP Student Conference, 2025)
PT Selaras Simpati Nusantara is a company engaged in Heavy Equipment Rental Contractor Services and Construction Services in Palembang, Indonesia. The company is located at Komplek Sapta Indah Town House, Jl. Seduduk Putih No.F9, 8 Ilir, Ilir Timur II District, Palembang City, South Sumatra 30164. PT Selaras Simpati Nusantara has 52 employees, consisting of 20 permanent employees and 32 contract employees. The company is divided into several main divisions, including the Finance Division with 6 employees, the Operations Division with 3 employees, the Engineering Division with 5 employees, and the General Division with 2 employees. Currently, the company still uses a manual recording system for various HR administrative processes, such as attendance, recruitment, leave applications, permits, and employee data recording. This manual system causes several issues, including a high risk of data loss, inaccurate recording, delays in administrative processes, and difficulties in searching and managing employee data. This study aims to develop a web-based HR information system to improve efficiency, accuracy, and ease of HR data management. The method used is the Rational Unified Process (RUP), which consists of inception, elaboration, construction, and transition. The result of this study is a web-based application capable of automating HR administrative processes, accelerating workflows, and making them more efficient, transparent, and well-organized.